Implications of spin vortex scenario for 1/8-doped lanthanum cuprates - Fine, Boris V. (Journal of superconductivity and novel magnetism, 2011)
A superlattice of spin vortices has been proposed in an earlier article as an alternative to the stripe interpretation of spin modulations in 1/8-doped lanthanum cuprates. The present article addresses several additional characteristics of the spin vortex lattice, namely: (i) the nature of extended charge states; (ii) the position of neutron spin peaks as a function of doping; and (iii) the absence of higher-order spin harmonics. All these characteristics afford straightforward connection to the experimental results produced by angle-resolved photoemission spectroscopy, resistivity measurements, and neutron scattering.